2017
DOI: 10.21859/sija-1104518
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Efficacy and Quality of Life Among Elderly People

Abstract: Objectives Self-Efficacy is an important variable in the field of elderly, to which little attention has been paid. Quality of Life (QoL) is also one of the most important factors of human development. This study aimed to determine and investigate the relationship between self-efficacy and QoL among elders residing in Tehran nursing homes in 2015.Methods & Materials In this cross-sectional descriptive-analytic study, the statistical population comprised the residents of nursing homes, especially catering to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
3
9
1
Order By: Relevance
“…The correlation between QoL and self-efficacy was positive and significant. The results of the study by Peters et al ., as well as Shaabani et al ., are consistent with the results of this study,[ 30 31 ] which conclude that the self-efficacy status and QoL of people can be improved in different dimensions by developing strategies and programs. In Iran, access to online health information is not readily comprehensible and easy for audiences, while this aspect of health information is emphasized in other countries, and some health associations and organizations such as the Medical Library Association and British Medical Association (BMA) have introduced reputable and high-quality health websites.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between QoL and self-efficacy was positive and significant. The results of the study by Peters et al ., as well as Shaabani et al ., are consistent with the results of this study,[ 30 31 ] which conclude that the self-efficacy status and QoL of people can be improved in different dimensions by developing strategies and programs. In Iran, access to online health information is not readily comprehensible and easy for audiences, while this aspect of health information is emphasized in other countries, and some health associations and organizations such as the Medical Library Association and British Medical Association (BMA) have introduced reputable and high-quality health websites.…”
Section: Discussionsupporting
confidence: 92%
“…The current study revealed a relation between education and QOL of elderly people, which had also been reported in studies by Luthy et al, 43 Shaabani et al, 44 Lee et al, 45 Ganesh Kumar et al, 37 and Hongthia et al 46 Education enhances self-confidence and knowledge about health, which contributes to more mental and physical health and better QOL.…”
Section: Discussionsupporting
confidence: 86%
“…The studies assumed that there was a direct cause and effect relationship between the psychological mechanism of a sense of self-efficacy and behavior. It was recognized that understanding a sense of self-efficacy in elderly people can contribute to a better understanding of their capabilities, limitations and needs [ 6 ]. Numerous studies having been conducted in recent years among students at the University of the Third Age (UTA) confirm that, compared to their peers who do not show such activity, active UTA students have a higher level of confidence related to the chances of achieving their goals.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently included in personal resources, which are available to every human being to a higher or lower degree. A sense of self-efficacy allows one to anticipate intentions and actions in various areas of activity—including health behaviors—as it becomes an implication of currently undertaken actions and the intention to engage in health activities [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation